IMPROVING THE EIGHT GRADE STUDENTS’ SPEAKING ACHIEVEMENTAT SMP N 26 PALEMBANG BY USING GAMES - Budiyanto, Darmawan (UNIVERSITAS TRIDINANTI PALEMBANG, 2018)
The aims of this research were 1) to describe what extent games improve speaking achievement; 2) to identify the situation when games are implemented in the speaking class. The subject of the study was the students of class 8.5 of State of Junior High School 26 Palembang. The research was carried out in two cycles, they were identifying the problem, planning the action, implementing the action, observing the action, reflecting the action and revising the plan. Data were collected through survey, observation and interview. The researcher analyzed qualitative data through constant comparative method. The quantitative data were analyzed by using descriptive statistic, and collected by conducting pre-test and post-test, are analyzed to know the improvement of students’ speaking achievement. The mean score of pre-test is 4.08. This score improved to 5.31 in post-test 1 and even higher in post-test 2 that is 6.05. From the qualitative data, the research finding shows that students’ speaking achievement improved in the term of ability in: 1) answering the teacher’s questions orally, 2) identifying the words and grammar used in the expression, 3) making sentences using appropriate grammar and vocabulary, and 4) expressing their idea. Keywords: speaking achievement games, classroom action research.